Identification of a novel ligand for the ATAD2 bromodomain with selectivity over BRD4 through a fragment growing approach. Issue 11 (22nd February 2018) - Miller, Duncan C.; Martin, Mathew P.; Adhikari, Santosh; Brennan, Alfie; Endicott, Jane A.; Golding, Bernard T.; Hardcastle, Ian R.; Heptinstall, Amy; Hobson, Stephen; Jennings, Claire; Molyneux, Lauren; Ng, Yvonne; et al.
Abstract : Structure-guided expansion of a fragment hit for the ATAD2 bromodomain enabled improvement in ATAD2 inhibition and selectivity over BRD4. Abstract : ATAD2 is an ATPase that is overexpressed in a variety of cancers and associated with a poor patient prognosis. This protein has been suggested to function as a cofactor for a range of transcription factors, including the proto-oncogene MYC and the androgen receptor. ATAD2 comprises an ATPase domain, implicated in chromatin remodelling, and a bromodomain which allows it to interact with acetylated histone tails. Dissection of the functional roles of these two domains would benefit from the availability of selective, cell-permeable pharmacological probes. An in silico evaluation of the 3D structures of various bromodomains suggested that developing small molecule ligands for the bromodomain of ATAD2 is likely to be challenging, although recent reports have shown that ATAD2 bromodomain ligands can be identified. We report a structure-guided fragment-based approach to identify lead compounds for ATAD2 bromodomain inhibitor development. Our findings indicate that the ATAD2 bromodomain can accommodate fragment hits ( M r < 200) that yield productive structure–activity relationships, and structure-guided design enabled the introduction of selectivity over BRD4.